2014
DOI: 10.1071/wf12106
|View full text |Cite
|
Sign up to set email alerts
|

Social preferences for fuel break management programs in Spain: a choice modelling application to prevention of forest fires

Abstract: This article reports on an economic valuation study of alternative fire prevention programs in the province of Málaga, southern Spain. The main aim of this study was to explore the social preferences for several forest fire prevention management issues. Fuel break programs were presented that differed in terms of cleaning technique (controlled grazing, prescribed burning and mechanical treatments), design (from traditional linear unshaded fire breaks to more landscape and environmentally friendly structures, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…Different studies conducted in the Mediterranean region have shown that, when adequately managed, targeted grazing can constitute a suitable and effective tool for reducing biomass [10,[12][13][14]. It may also produce significant savings for fire prevention services in comparison to the costs of mechanical biomass reduction, and support many other environmental services [15][16][17]. The use of grazing to reduce understory biomass does also attempt to reconcile the use of products and services from the natural environment and pursues efficient land use through the production of meat and milk [14].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies conducted in the Mediterranean region have shown that, when adequately managed, targeted grazing can constitute a suitable and effective tool for reducing biomass [10,[12][13][14]. It may also produce significant savings for fire prevention services in comparison to the costs of mechanical biomass reduction, and support many other environmental services [15][16][17]. The use of grazing to reduce understory biomass does also attempt to reconcile the use of products and services from the natural environment and pursues efficient land use through the production of meat and milk [14].…”
Section: Introductionmentioning
confidence: 99%
“…The drawback of this approach is that the scientific link between action and end effects is many times uncertain and difficult to prove. The study by Varela et al (2014aVarela et al ( , 2014b was developed in a Mediterranean context and conveys simultaneously information on fire prevention and outcomes related to the expected burnt area. Thus, respondents expressed their preferences both for causal attributes (design of fuel breaks and cleaning techniques) and for effect attributes (density of fuel breaks and expected burnt area).…”
Section: Discussionmentioning
confidence: 99%
“…They compare WTP estimates between wildland urban interface (WUI) and urban residents and found similar results for both subsamples with mean WTP for thinning higher than for prescribed burning in all samples. Varela et al (2014aVarela et al ( , 2014b conducted a CM survey in the province of Malaga (southern Spain) where respondents were asked to make trade-offs among fuel break management scenarios, each of them showing different combinations of fuel break cleaning technique, design of fuel breaks and density of the fuel break network (coupled with an expected decrease in burnt area). The density of the fuel break network is the attribute that determined preferences to a greater extent.…”
Section: The Role Of Economic Valuation In Fire Prevention Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to consider developing econometric methods for rank-ordered data, to complement the continual effort to understand better and improve ranking survey designs (Caparrós, Oviedo and Campos, 2008;Chang, Lusk and Norwood, 2009;Scarpa et al, 2011;Akaich, Nayga, and Gil, 2013;Louviere, Flynn and Marley, 2015). The existing approach to analyzing rank-ordered data usually exploits extensions and variants of the exploded logit (Chapman and Staelin, 1982), both within (Chang, Lusk and Norwood, 2009;Scarpa et al, 2011;Resano, Sanjuan and Albisu, 2012;Othman and Rahajeng, 2013;Varela et al, 2014) and outside (Fok, Paap and Van Dijk, 2012;Yoo and Doiron, 2013) the environmental valuation literature. Our strategy adds to the empirical practitioner's toolkit an approach building on the nested rank-ordered logit of Dagsvik and Liu (2009) that allows for more plausible substitution patterns.…”
Section: Introductionmentioning
confidence: 99%